Neuroplasticity-Based Cognitive and Linguistic Skills Training Improves Reading and Writing Skills in College Students - Rogowsky, Beth; Papamichalis, Pericles; Villa, Laura; Heim, Sabine; Tallal, Paula (Frontiers in Psychology, 2013)
This study reports an evaluation of the effect of computer-based cognitive and linguistic training on college students’ reading and writing skills. The computer-based training included a series of increasingly challenging software programs that were designed to strengthen students’ foundational cognitive skills (memory, attention span, processing speed, and sequencing) in the context of listening and higher level reading tasks. Twenty-five college students (12 native English language; 13 English Second Language) who demonstrated poor writing skills participated in the training group. The training group received daily training during the spring semester (11 weeks) with the Fast ForWord Literacy (FFW-L) and upper levels of the Fast ForWord Reading series (Levels 3, 4 and 5). The comparison group (n=28) selected from the general college population did not receive training. Both the training and comparison groups attended the same university. All students took the Gates MacGinitie Reading Test (GMRT) and the Oral and Written Language Scales (OWLS) Written Expression Scale at the beginning (Time 1) and end (Time 2) of the spring college semester. Results from this study showed that the training group made a statistically greater improvement from Time 1 to Time 2 in both their reading skills and their writing skills than the comparison group. The group who received training began with statistically lower writing skills before training, but exceeded the writing skills of the comparison group after training.